Leading Commodity Analysis of Capture Fisheries in Karimunjawa National Park - Irnawati, Ririn; Simbolon, Domu; Wiryawan, Budy; Murdiyanto, Bambang; Nurani, Tri Wiji (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Karimunjawa National Parks (TNKJ) is a marine conservation area which has 111.625 ha area with the majority ofresidents work as fishermen. Utilization of traditional fisheries zone intended for fishing activities. Therefore, fishing activities in TNKJ should be conducted in accordance with the principles of conservation. The aim of this study was to determine the winning fish fishery commodities in TNKJ. The selection of commodities was done by using comparative performance index (CPI). Analysis of potential fish resources is done with bioeconomic model. Optimizing the amount of fishing equipment was done by using linear goal programming (LGP). Feasibility of the business conducted by financial analysis. The results showed commodities TNKJ reef fisheries are pompano, and for pelagic fisheries are anchovies. Reef fish resource potential of 174 tons / year and pelagic fish of 22 069 tons / year. Appropriate fishing technologies for reef fisheries is the fishing rod elongation and traps, while for the pelagic fishery and gillnet fishing minnows on trolling lines. Financial analysis shows that all fishing gear is still viable to continue the effort. Key words: Selection commodities, fishing activities, Karimunjawa National Parks